(untitled) (Pedagogy of Higher and Secondary Education, 2011)
The article deals with the problem concerning linguistic and didactic difficult foreing language studies and the ways og their overcoming as the means of students’ independence forming in higher educational establishments of the I-II sccreditation levels.